2007
DOI: 10.1098/rspb.2007.1006
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of species: implications for macroevolutionary and macroecological studies

Abstract: Knowing the geographic extents of species is crucial for understanding the causes of diversity distributions and modes of speciation and extinction. Species geographic ranges are often viewed as approximately constant in size in geological time, even though climate change studies have shown that historical and modern species geographic distributions are not static. Here, we use an extensive global microfossil database to explore the temporal trajectories of geographic extents over the entire lifespan of marine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
171
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(178 citation statements)
references
References 43 publications
(63 reference statements)
6
171
0
1
Order By: Relevance
“…Furthermore, range sizes have been shown to vary systematically over the geologic history of lineages (Foote 2007;Foote et al 2007;Liow and Stenseth 2007;Liow et al 2010;Tietje and Kiessling 2013), with many lineages exhibiting protracted intervals of range expansion and contraction separated by short-lived peaks in range size, which could also result in little phylogenetic structure to range size. Among Devonian terebratulide genera, however, we show that the distribution of geographic range sizes over the phylogeny is consistent with that expected if range size was evolving under Brownian motion over the Devonian history of the clade.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, range sizes have been shown to vary systematically over the geologic history of lineages (Foote 2007;Foote et al 2007;Liow and Stenseth 2007;Liow et al 2010;Tietje and Kiessling 2013), with many lineages exhibiting protracted intervals of range expansion and contraction separated by short-lived peaks in range size, which could also result in little phylogenetic structure to range size. Among Devonian terebratulide genera, however, we show that the distribution of geographic range sizes over the phylogeny is consistent with that expected if range size was evolving under Brownian motion over the Devonian history of the clade.…”
Section: Discussionmentioning
confidence: 99%
“…They found that almost all species showed considerable variation in the size of their ranges throughout the course of their existence (Figure 10; see also Liow and Stenseth, 2007).…”
Section: Phylogenetic Approaches Are Not Suitable For Traits That Evomentioning
confidence: 99%
“…Thus, existing studies do not readily allow direct comparisons of past losses of EH with those predicted for anthropogenic extinctions. Although temporal durations of species in the fossil record are more difficult to estimate reliably than those of higher taxa (23), a number of paleontological studies have used fossil species successfully to test important evolutionary and biogeographic hypotheses (21,(51)(52)(53)(54)(55)(56) as well as various aspects of the extinction process (57)(58)(59). With the increasing availability of large, taxonomically standardized paleontological databases, analyses of age selectivity of extinctions at the species level, such as the one undertaken here, are now feasible, especially on regional scales.…”
Section: Discussionmentioning
confidence: 99%